THE EFFECTIVENESS OF USING POINT, ILLUSTRATION, EXPLANATION (PIE) STRATEGY THE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT ON TENTH GRADE AT SMA RK SERDANG MURNI LUBUK PAKAM - Br Siregar, Aseantri Cian; Napitupulu, Fenty D.; Saragih, Christina N (Jurnal Teknologi Mesin UDA, 2025)
This research focuses on finding out The Effectiveness of Point, illustration, explanation (PIE) Strategy on students' writing ability. The purpose of this study is to find out whether the PIE strategy is effective so that it affects students' writing ability. This research was conducted as an applied experimental quantitative research type. The sample of this study consisted of X grade students at SMA Rk Serdang Murni Lubuk Pakam. The author took class X-2 consisting of 16 students as an experimental class using the PIE (Point, illustration, explanation) strategy and class X-1 consisting of 16 students as a control group using conventional methods or without using the PIE Point, illustration, explanation) strategy. the population of this study was 32 students consisting of class X. The author took two classes as samples randomly to see the effect of the effectiveness of the PIE Strategy (Point illustration, explanation) to develop students' ability in writing. The data was collected by giving a writing test which is an essay test. This test was divided into two tests: pre-test and post-test for the experimental and control classes. The average pre-test score in the experimental class was 58,25 and the post-test score was 84,18. The average pre-test score in the control group was 57,56 and the post-test score was 68,56. This shows that the average score in the experimental group was higher than the control group. The result is t-calculated > t-table with a significance level of p = 0.05 (8,94 > 2.042). The alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. It is suggested that English subject teachers apply the PIE (Point, Illustration, Explanation) strategy as an alternative teaching tool to help the writing skills of class X students of SMA Rk Serdang Murni Lubuk Pakam.